Refraction changes in the anterior and posterior corneal surfaces during the early postoperative period following sinus trabeculectomy - V.V. Averich; A.V. Volzhanin; G.B. Egorova (РМЖ "Клиническая офтальмология")
V.V. Averich, A.V. Volzhanin, G.B. Egorova Krasnov Research Institute of Eye Diseases, Moscow, Russian Federation Aim: to evaluate keratotopography of the anterior and posterior corneal surfaces in the early postoperative period following sinus trabeculectomy (STE). Patients and Methods: the study included 45 patients (45 eyes) with primary open angle glaucoma, stages II-III, who underwent trabeculectomy, as it was impossible to reduce intraocular pressure (IOP) by the prescribed medications. Corneal topographic parameters of the anterior and posterior corneal surfaces were evaluated with Scheimpflug camera before surgery, 1 week and 1 month after STE. Results: one week after surgery, general and corneal astigmatism increased (0.32 and 1.0 diopters, respectively). An increase in the anterior corneal curvature was usually associated with the vertical meridian and in the posterior corneal curvature — with the horizontal meridian. Topographically, there was an asymmetric steeping of individual corneal segments that cannot be explicitly classified. One month after the operation there was a trend to flattening of the anterior corneal surface and to increasing of the posterior curvature astigmatism by 0.5 diopters. Measurements taken with auto kerato-refractometer demonstrated that general astigmatism reduced by 0.69 diopters. However, the measurements revealed a 1.5-fold increase in mean corneal astigmatism compared to baseline. One week after surgery, the spherical component increased by 0.36 diopters, and following one month — by 0.62 diopters. The corneal thickness did not change during the entire follow-u p period. Keratometric measurements of the anterior and posterior corneal surfaces strongly correlated at all follow-up evaluation points. There was a correlation between Scheimpflug imaging and measurements taken with auto kerato-refractometer. At different time points, a relationship was found between the corneal astigmatism and the mean curvature or the steep meridian of the anterior and posterior corneal surfaces. Conclusion: STE causes an induced astigmatism as it affects both the anterior and posterior corneal curvatures. Since the effect of induced astigmatism on the cornea is varying, it is not possible to find appropriate classification for such cases, and, as a rule, the astigmatism cannot be controlled with optical correction methods. Keywords: glaucoma, trabeculectomy, cornea, refraction, posterior corneal curvature. For citation: Averich V.V., Volzhanin A.V., Egorova G.B. Refraction changes in the anterior and posterior corneal surfaces during the early postoperative period following sinus trabeculectomy. Russian Journal of Clinical Ophthalmology. 2023;23(1):27–32 (in Russ.). DOI: 10.32364/2311-7729-2023-23-1-27-32.